The DNA Expansion Programme and Criminal Investigation - McCartney, Carole (The British journal of criminology, 2006)
DNA evidence is a powerful investigative tool, able to incriminate as well as exculpate. Yet, increasingly common portrayals of DNA as being able to solve crimes almost instantaneously, beyond any doubt, even from beyond the grave', may overstate the degree to which DNA currently assists in criminal investigations. Strong government support, and financial investment in the DNA Expansion Programme, have been bolstered by repeated legislative extensions of police powers to obtain and retain DNA samples. Despite this, DNA evidence remains marginal in terms of assisting with overall criminal detections and experts now suggest that the massive National DNA Database expansion has not resulted in the improvement in detection rates originally anticipated. This paper also suggests potential concerns over the tactical' use of DNA evidence during suspect interviews, and the risk of abbreviated police investigations. Insufficiently forensically aware' police officers may resort to DNA evidence in lieu of proper detective work, with literature on case construction' informing analysis of potential pitfalls of early reliance on DNA results, which may increase the risk tunnel vision' in criminal investigations